Pengembangan Evidence Monitoring Tingkat PH dan Kekeruhan Air Untuk Menentukan Kelayakan Konsumsi Air - Andi Fatri; Muhammad Basri; Untung Suwardoyo (Jurnal Informatika, 2024)
Development of Evidence Monitoring of PH Levels And Water Turbidity to Determine the Feasibility of Water Consumption. (Supervised by Muhammad Basri and Untung Suwardoyo). The most common method for detecting water quality parameters is by manually collecting samples and sending them to a laboratory for detection and analysis. However, with the advancement of time and technology, this method has become somewhat less relevant due to its manual nature. For that reason, a study was conducted titled "Development of Evidence-Based Monitoring for pH and Turbidity Levels to Determine Drinking Water Feasibility." This study aims to develop a monitoring process that also simplifies the assessment of water feasibility through an automated system, making the process more efficient and relevant. This monitoring system uses two indicators: turbidity and pH. The system is developed using a pH sensor SEN0161-V2 and a turbidity sensor DF Robot-SEN0189, with an ESP32 microcontroller.(Permenkes RI, 2010) It is designed to monitor changes in values in real time, which are then displayed through an Android application. The device is also equipped with a filtration system. Test results showed a change in turbidity levels from an initial value of 29.8 NTU (not suitable for consumption) to 4.8 NTU (suitable for consumption), within a water filtration cycle duration of 24 minutes and 56 seconds.